Compressed Genotyping - Erlich, Y.; Gordon, A.; Brand, M.; Hannon, G.J.; Mitra, P.P. (IEEE transactions on information theory, 2010)
Over the past three decades we have steadily increased our knowledge on the genetic basis of many severe disorders. Nevertheless, there are still great challenges in applying this knowledge routinely in the clinic, mainly due to the relatively tedious and expensive process of genotyping. Since the genetic variations that underlie the disorders are relatively rare in the population, they can be thought of as a sparse signal. Using methods and ideas from compressed sensing and group testing, we have developed a cost-effective genotyping protocol to detect carriers for severe genetic disorders. In particular, we have adapted our scheme to a recently developed class of high throughput DNA sequencing technologies. The mathematical framework presented here has some important distinctions from the ¿traditional¿ compressed sensing and group testing frameworks in order to address biological and technical constraints of our setting.